Oleanane-type triterpenoid saponins from Lysimachia fortunei Maxim. (March 2018) - Zhang, Shu-Lin; Yang, Zi-Ni; He, Cui; Liao, Hai-Bing; Wang, Heng-Shan; Chen, Zhen-Feng; Liang, Dong
Abstract: Six previously undescribed oleanane-type triterpenoid saponins, fortunosides A–F, together with six known ones, were isolated from the aerial parts of L ysimachia fortunei Maxim. Their structures were established by spectroscopic data analyses (1D, 2D-NMR and HRESIMS) and chemical methods. All isolated triterpenoid saponins were evaluated for their cytotoxicity against four human liver cancer cell lines (SMMC-7721, Hep3B, HuH7, and SK-Hep-1). Three saponins with the aglycone protoprimulagenin A exhibited moderate cytotoxicity against all of the tested human cancer cell lines, with IC50 values ranging from 4.76 to 15.12 μM. Graphical abstract: Twelve oleanane-type triterpenoid saponins, including six previously undescribed ones, were isolated from the aerial parts of L ysimachia fortunei Maxim. Three saponins with the aglycone protoprimulagenin A exhibited moderate cytotoxicity against all of the tested human liver cancer cell lines. Highlights: Six previously undescribed triterpenoid saponins were isolated from Lysimachia fortunei. Their structures were elucidated by spectrometric data analyses and chemical methods. Saponins with the aglycone protoprimulagenin A exhibited moderate cytotoxicity.